Recommendation on portfolio return optimization based on price earning ratio / Suzelawati Basir - Basir, Suzelawati (2007)
The purpose of this study is to determine the effect of price earning ratio (PE) to the efficient portfolio in the Malaysia market. Then, it is important to find the appropriate weight for each asset and calculate the risk and expected return. Beside that this study also compared the performance within two period which at the highly market volatile (period 1) and stable market (period 2). The other objective of this research is to make recommendation of efficient portfolio to investor. To complete this study, monthly data from January 1997 until July 2007 of 60 stocks with low and high PE ratio will derived from the consumer product and the construction sector in the main board and second board in Bursa Malaysia. Efficient portfolio will be measured by using the risk and expected return. This study also will use portfolio optimization method. The optimum return of the stock will be recommended at the end of this study. To select which company are included into portfolio optimization, Cut-off-Rate (C* ) were used. The appropriate weights also have determined in order to gain the optimal return. From this Study, high PE ratio under construction sector at period 1 and low PE ratio for construction sector in period 2 is the lowest risk compare to other portfolio.